Expression and Clinical Implications of Cysteine Cathepsins in Gallbladder Carcinoma - Mehra, Siddharth; Panwar, Rajesh; Thakur, Bhaskar; Yadav, Rajni; Kumar, Manish; Singh, Ratnakar; Dash, Nihar Ranjan; Sahni, Peush; Chauhan, Shyam S. (Frontiers in Oncology, 2019)
Background Gallbladder carcinoma (GBC) exhibits poor prognosis due to its detection at an advanced stage. Upregulation of lysosomal cysteine proteases cathepsin L (CTSL) and cathepsin B (CTSB) has been implicated in several tumorigenic processes. However, no such information in GBC was available. Therefore, the present study was planned to investigate the expression and clinical significance of these cathepsins in GBC. Methods Activities of CTSL and CTSB were assayed in the gallbladder (GB) tissues obtained from GBC patients (n=43) and control subjects (n=69). Protein and mRNA levels were quantified using immunohistochemistry and real-time PCR (qPCR), respectively. Finally, serum levels of CTSL and CTSB were estimated by ELISA. Receiver operating characteristic (ROC) curve analysis was used for the assessment of sensitivity, specificity, and diagnostic accuracy of these cysteine cathepsins in GBC. The association of combined CTSL and CTSB activity with overall survival was assessed using Kaplan Meier survival analysis. Results The expression and activity of both CTSL and CTSB were significantly increased (p<0.050) in tumors of GBC patients. Enzymatic activity of CTSL+B and CTSB exhibited a strong positive association with tumor stage and lymph node involvement in GBC (p<0.050). Interestingly, the elevated activity of combined CTSL+B was also associated with increased mortality in these patients. Furthermore, significantly enhanced levels of serum CTSL and CTSB were also observed in GBC (p<0.050) as compared to controls. ROC analysis revealed high diagnostic significance of serum CTSB and CTSL for distinguishing GBC patients from controls with an area under the curve AUC of 82% and 77% respectively. Conclusion This study, for the first time, demonstrates the clinical significance of CTSL and CTSB overexpression in GBC. Our findings may help improve the clinical management of this carcinoma.